Supervisor–subordinate Guanxi violations: Trickle-down effects beyond the Dyad. Issue 5 (December 2016) - Zhu, Yanhan; Li, Diwan
Abstract This paper explores the trickle-down effects of two kinds of supervisor–subordinateguanxi violations (instrumental and socio-emotional) beyond the dyad in Mainland China. The results showed that relative to a situation of no violation, both instrumental and socio-emotional supervisor–subordinateguanxi violations were associated with poorer job performance, more organizational retaliatory behavior, and stronger work–family conflict. Furthermore, organizational commitment mediated differently the relationships between the two kinds of supervisor–subordinateguanxi violations and relevant outcomes. We show that supervisor–subordinateguanxi violations can exert influences on subordinates in the work context and beyond, based on the trickle-down model.